Boiler ash as catalyst for the catalytic synthesis of organic carbonates - Vidhyaa, Paroo Indran (2016)
Over the years production of crude glycerol has been in an increasing pattern due to the rapid growth of biodiesel industry. Therefore, the market value of glycerol has dropped drastically in recent years. To overcome this problem, the conversion of glycerol into fine chemical such as glycerol carbonate through an economical catalytic synthesis route using boiler ash as catalyst was carried out in this study. Besides, Malaysia is the second largest oil palm producer in the world and about 4 million tons of boiler ash is produced annually from incineration of palm fruits, palm kernels, palm shells and palm fibres which contains variety of interesting metal elements. A series of catalysts were prepared using various calcination temperatures and through catalytic testing, the boiler ash calcined at 900 oC under static air (BA 900) was identified as the most active catalyst. The highest catalytic activity obtained resulted in an average of 93.6 ± 0.4 % conversion of glycerol, 90.1 ± 1.0 % selectivity of glycerol carbonate and 84.3 ± 1.1 % yield of glycerol carbonate at optimum reaction conditions of 150 °C, 4 h, molar ratio of 1:1.5 (glycerol: urea) plus stirring rate of 340 rpm. Potassium silicate (K2SiO3) present in boiler ash subsequently promoted the selective conversion of glycerol carbamate intermediate to glycerol carbonate at an accelerated manner in which K+ acted as weak Lewis acid while the SiO3 2- as conjugated basic site. It was found that, K+ activates the carbonyl group of urea while the conjugated basic SiO3 2- activates the hydroxyl group of glycerol to form glycerol carbonate. The turnover frequency (TOF) value calculated for both BA 900 (126.5 mmol/ g.cat.h-1) and K2SiO3 (125.6 mmol/ g.cat.h-1) were comparable, thus confirming similar active sites responsible for catalytic reaction. Although, studies using direct utilisation of industrial crude glycerol revealed that the catalyst is feasible to produce glycerol carbonate, the presence of impurities at certain amount in crude glycerol affected the catalytic activity. Boiler ash is also a versatile catalyst to synthesise ethylene carbonate and propylene carbonate. It was evidently proven that boiler ash showed similar catalytic pathway in synthesis of the three different carbonates. The current study pioneers in introducing catalyst derived from waste for the production of organic carbonate. It also proposes new scheme of mechanistic pathway at an accelerated manner for the synthesis of organic carbonates while proposing direct utilisation of crude glycerol without prior purification. In concise, the studies employed is near to a complete green synthesis approach as it suggests proper utilisation of waste boiler ash as catalyst and crude glycerol as feedstock.